The Critical Role of PI3K-AKT-mTOR Pathway for IL-15 Induced NK Cell Effector Responses - Nandagopal, Neethi (Université d'Ottawa / University of Ottawa, 2014)
Natural killer (NK) cells were so named for their uniqueness in killing certain tumor and virus-infected cells without prior sensitization unlike T lymphocytes. NK cells possess a myriad of activation receptors and cytokine receptors that allow them to recognize stress ligands on infected/tumor cells and respond to the cytokines produced during the inflammatory process. Upon activation, NK cells produce pro-inflammatory cytokines, cytotoxic granules and chemokines to recruit other cells which ultimately result in killing of target cells. These functions of NK cells are modulated in vivo by several immune mediators; IL-15 being the most potent in enabling NK cell homeostasis, maturation and activation. Indeed, IL-15 knockout mice have no detectable NK cells. During microbial infections, NK cells stimulated with IL-15 display enhanced cytokine responses. This priming effect has previously been shown with respect to increased IFN-γ production in NK cells upon IL-12 and IL-15/IL-2 co-stimulation. In this study, I explored if this effect of IL-15 priming can be extended to other cytokines and observed enhanced NK cell responses to stimulation with IFN-, IL-21, IL-2 and IL-4 in addition to IL-12. Notably, we also observed elevated IFN-γ production in primed NK cells upon stimulation through the Ly49H activation receptor. IL-15 treatments induced NK cell proliferation, enhanced NK cell responses to activating stimuli and equipped them with cytotoxic granules thereby “readying” them for battle against infections and tumors. Here, we try to understand the signaling mechanisms underlying IL-15 treatments that activate NK cells. Currently, the fundamental processes required for priming and whether these signaling pathways work collaboratively or independently for NK cell functions are poorly understood. To identify the key signaling events, we examined IL-15 priming on NK cells in which the pathways emanating from IL-15 receptor activation were blocked with specific inhibitors. Our results demonstrate that the PI3K-AKT-mTOR pathway is indispensable for cytokine responses in IL-15 primed NK cells. Furthermore, this pathway is also implicated in a broad range of IL-15 induced NK cell effector functions such as proliferation and cytotoxicity. Given that NK cells are critical for control of viral infections like murine cytomegalovirus (MCMV), we decided to analyze the consequences of blocking the PI3K-AKT-mTOR pathway in NK cells on its anti-viral responses. Likewise, NK cells from mice treated with rapamycin to block the mTOR pathway displayed defects in proliferation, IFN-γ and granzyme B production resulting in elevated viral burdens upon MCMV infection. Taken together, our data demonstrates the requirement of PI3K-mTOR pathway for enhanced NK cell functions by IL-15. It also shows that IL-15 primes NK cell responses to several cytokines and to Ly49H activation receptor stimulation. To our knowledge this is first report to demonstrate the requirement of mTOR activity in NK cells for efficient control of acute MCMV infections; thereby coupling the metabolic sensor mTOR to NK cell anti-viral responses.
Keywords: IL-15; MTOR; RAPAMYCIN; NK CELLS; PRIMING